Expression of PLK1 and survivin in non-Hodgkin's lymphoma treated with CHOP - Liu Lin; Zhang Min; Zou Ping (Acta Pharmacologica Sinica; Vol 29, No 3 (March 2008): Acta Pharmacologica Sinica, 2016)
Aim: The present study was designed to investigate the expression of Polo-like kinase 1 (PLK1) and survivin in non-Hodgkin's lymphoma (NHL). Methods: The expression of PLK1 and survivin were detected with immunohistochemical techniques. Results: The expression rate of PLK1 and survivin were 63.6% (56/88) and 79.5% (70/88) in NHL, respectively. PLK1 expression correlated with systemic symptoms, lactate dehydrogenase levels, and international prognostic index scores in B-NHL and T-NHL, while survivin did not. Conclusion: PLK1 and survivin are both overexpressed in NHL. There is a significant relationship between the overexpression of PLK1 and clinical features.